Procyanidin B2 Activates PPARγ to Induce M2 Polarization in Mouse Macrophages - Tian, Ying; Yang, Chunmiao; Yao, Qinyu; Qian, Lei; Liu, Jia; Xie, Xinya; Ma, Wen; Nie, Xin; Lai, Baochang; Xiao, Lei; Wang, Nanping (Frontiers in Immunology, 2019)
Procyanidins, a subclass of flavonoids found in commonly consumed foods, possess potential anti-inflammatory activity. Manipulation of M1/M2 macrophage homeostasis is an effective strategy for the treatment of metabolic inflammatory diseases. The objective of this study was to determine the effect of procyanidins on macrophage polarization. Procyanidin B2 (PCB2), the most widely distributed natural procyanidins, enhanced the expressions of M2 macrophage markers (Arg1, Ym1, and Fizz1). PCB2 activated peroxisome proliferator-activated receptor γ (PPARγ) activity and increased the expressions of PPARγ target genes (CD36 and ABCG1) in macrophages. Inhibition of PPARγ using siRNA or antagonist GW9662 attenuated the PCB2-induced expressions of M2 macrophage markers. In addition, we identified cognate PPAR-responsive elements (PPREs) within the 5'-flanking regions of the mouse Arg1, Ym1, and Fizz1 genes. Furthermore, macrophages isolated from db/db diabetic mice showed lower expressions of M2 markers. PCB2 effectively restored the Arg1, Ym1, and Fizz1 expressions in a PPARγ-dependent manner. These findings support the notion that PCB2 regulated macrophage M2 polarization via the activation of PPARγ. Our results provide a new mechanism by which procyanidins exert their beneficial anti-inflammatory effects.